The effect of activated charcoal on the adsorption of growth regulators and treat browning phenomenon of date palm Phoenix dactylifera L. in vitro (Journal of the College of Basic Education, 2022)
The study was carried out on Date palm (the variety Zahdi ) (Phoenix dactylifera L.). The effect of activated charcoal was studied on the adsorption of growth regulators to the auxins : α-Naphthalene acetic acid (NAA) , β-Naphthyloxy acetic acid (NOA) , Indol-3-acetic acid (IAA) and the cytokinin N-(2-isopentyl) adenine (2,ip) by culturing the samples on culture media which devoided of activated charcoal and determination of the optimum concentration for the initiation of primary buds in comparsion with the concentrations of growth regulators in media containing activated charcoal. The results showed that the most favorable concentrations are 1, 1, and 1 mg/L for the auxins NAA, NOA, IAA, respectively, and 0.1 mg/l for the cytokinin 2,ip, when the samples were cultured on culture media devoided of activated charcoal. Results have also revealed that curing of the browning phenomenon become by freezing prior to culturing at temperature -18 ºC for 30 days instead of using ; antioxidant solution (150 mg/L citric acid and 100 mg/L ascorbic acid) and using Polyvinyl pyrolidone (P.V.P.) , and adsorption factor for (activated charcoal). The freezing factor alone was more effective in controling the browning phenomenon than the other factor.Keywords : growth regulation . browning . date palm